Application of Critical Theory in the Systemic Cycle of Education Policy - Elaheh Valizadeh; Rohollah Eslami (Pizhūhish/nāmah-i Mabānī-i Ta̒līm va Tarbiyat.)
Public policy-making means the government in action, that is, what decisions the government makes in public matters, for which groups, with what tools, and what results are obtained from these decisions. Education policymaking means designing and implementing policies that the government uses in the field of education. Education policy in all countries is one of the three policy issues. Education is a socialization device for the government, and for this reason, governments use education as a public good to reproduce legitimacy. In this article, the issue is whether it is possible to organize the policy cycle based on critical theory. The policy cycle has stages such as system input, design, policy implementation and output, and evaluation and feedback. In this article, we try to examine the education policy cycle from a critical perspective by using the critical theories of Jürgen Habermas, Pierre Bourdieu, and Louis Althusser. The findings of the article show that critical theory is an approach that tries to organize a new space for educational policies in terms of public domain, communication wisdom, power fields, and the ideological structure of government. The article is the application of critical theory in the policy cycle of education, which can be used as a basis for future research.